Recommendations for enhancing IPCC technical guidance on assessing climate impacts and adaptation - Njuguna, Lucy; Rosenstock, Todd; Nowak, Andreea C. (2024)
At its 60th plenary session, the IPCC agreed to revise and update the 1994 technical guidelines for assessing climate impacts and adaptation. This working paper examines a potential approach for revising and advancing the guidelines, outlining key aspects that need to be considered and a potential framework for organizing the content.